PENGARUH KONSENTRASI NATRIUM METABISULFIT DAN LAMA PERENDAMAN TERHADAP KARAKTERISTIK BUBUK BUNGA KENIKIR (Tagetes erecta L.) - Darmawan, Komang Adi; Wartini, Ni Made; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 1 (2019): Maret, 2019)
Marigold powder can be used as natural orange dyes extract of marigold powder contain ?-carotene. The aim of this research was to investigate the effect of sodium metabisulfite (Na 2 S 2 O 5 ) concentration and soaking time on the characteristics of marigold flower powder and determine the best treatment of the concentration of sodium metabisulphite (Na 2 S 2 O 5 ) and soaking time to produce powdered marigold flowers. This research used factorial randomized block design with 2 factor experiments. The first factor is the concentration of sodium metabisulfite (Na 2 S 2 O 5 ) which consists of 3 levels: 2000, 2500, and 3000 ppm. The second factor is the soaking time which consists of 3 levels: 10, 20, and 30 minutes. The results of research showed that the treatment of sodium metabisulfite (Na 2 S 2 O 5 ) concentration take effect on water content, total carotenoid levels, brightness (L*), yellowish level (b*), and sulfite residue levels, but no effect to the level of redness (a*). The treatment of soaking time take effect on the levels of sulfite residues but no effect on water content, total carotenoid levels, brightness level (L*), yellowish level (b*), and redness level (a*). Soaking treatment in sodium metabisulfite (Na 2 S 2 O 5 ) solution with a concentration of 2500 ppm and soaking time of 10 minutes, is the best treatment to produce marigold flower powder with the characteristics of water content 11,40%, total carotenoid levels of 18.91%, brightness level (L*) 44.19, redness level (a*) 63.80, yellowish level (b*) 56.86, and sulfite residue levels of 182.40 ppm. Keywords : Tagetes erecta L, sodium metabisulfite, carotenoid, color.